Tourist Motivation as an Antecedent of Destination and Ecotourism Loyalty - Sinh Duc Hoang; Tien Phat Pham; Zuzana Tučková (Emerging Science Journal, 2022)
Objective: This study evaluates the role of tourist motivation in the determination of destination and ecotourism loyalty using push and pull motivation theory and the theory of planned behavior. The paper also analyses the mediating effects of satisfaction and destination image in the relationships between motivation and the two types of loyalty. Method/analysis: Primary data has been gathered from surveys involving 522 Vietnamese tourists traveling to the Bohemian Switzerland National Park in the Czech Republic. Data analysis was conducted using structural equation modeling (SEM) techniques in R. Findings: The findings support both direct and indirect positive associations between tourist motivation and destination and ecotourism loyalty. In terms of ecotourism loyalty, the effect is mediated by destination image. In terms of destination loyalty, the effect is mediated by satisfaction and destination image. Novelty/improvement: This study has further expanded the theory of planned behavior in the context of ecotourism by linking it to travel career pattern theory and functionalist theory. These are complementary theories that can explain the behavior of ecotourists and help operators and marketers adjust their strategies to attract and retain visitors to ecotourist destinations. Doi: 10.28991/ESJ-2022-06-05-014 Full Text: PDF